Star wars, the clone wars. The complete season two [videorecording (DVD)] - Lucas, George, 1944-; Kane, Tom, 1962- (Distributed by Warner Home Video, 2011)
This new TV series takes place immediately after the events of Star Wars Episode II: Attack of the Clones. The series follows Obi-Wan Kenobi and his apprentice, Anakin Skywalker, and introduces us to some new characters, such as Ahsoka Tano, a female Jedi Knight, as well as characters we already know. This title has been repackaged.